Bismuth (III) Telluride (Bi2Te3) topological insulator embed in PVA as passive Q-switcher at 2 micron region - Muhammad Apandi, Nur Hidayah; Ahmad, Fauzan; Zuikafly, Siti Nur Fatin; Ibrahim, Mohd Haniff; Harun, Sulaiman Wadi (Photonics Letters of Poland, 2016)
We demonstrate a passive Q-switched at 2 um region by integrating Bismuth (III) Telluride (Bi2/Te3) embedded in Polyvinyl Alcohol (PVA). Bi2Te3 was embedded in PVA by solution casting approach to develop a Bi2/Te3-PVA film and integrated in the laser cavity with ring configuration to generate pulse laser. The experimental works show that the proposed passive saturable absorber operates at input pump power ranges from 637 mW to 784 mW with central wavelength of 1957.6 nm. We observed the tunable repetition rate from 12.6 kHz to 26.1 kHz with the shortest pulse width of 2.22 us. The laser produces maximum instantaneous output peak power and pulse energy of 0.42 W and 0.94 uJ, respectively. Full Text: PDF References C. Zhao, H. Zhang, X. Qi, Y. Chen, Z. Wang, S. Wen, and D. Tang, "Ultra-short pulse generation by a topological insulator based saturable absorber", Appl. Phys. Lett. 101, 211106 (2012). CrossRef Z. C. Luo, M. Liu, H. Liu, X.-W. Zheng, A.-P. Luo, C.-J. Zhao, H. Zhang, S. C. Wen, and W.-C. Xu, "2GHz passively harmonic mode-locked fiber laser by a microfiber-based topological insulator saturable absorber", Opt. Lett. 38, 5212 (2013). CrossRef J. Lee, J. Koo, Y. M. Jhon, and J. H. Lee, "A femtosecond pulse erbium fiber laser incorporating a saturable absorber based on bulk-structured Bi2Te3 topological insulator", Opt. Express 22, 6165 (2014). CrossRef M. Jung, J. Lee, J. Koo, J. Park, Y. W. Song, K. Lee, S. Lee, and J. H. Lee, "A femtosecond pulse fiber laser at 1935 nm using a bulk-structured Bi2Te3 topological insulator", Opt. Express 22, 7865(2014). CrossRef Y. H. Lin, C. Y. Yang, S.-F. Lin, W. H. Tseng, Q. Bao, C. I. Wu, and G.R. Lin, "Soliton compression of the erbium-doped fiber laser weakly started mode-locking by nanoscale p-type Bi2Te3 topological insulator particles", Laser Phys. Lett. 11, 055107(2014). CrossRef J. Lee et al., "All-fiberized, passively Q-switched 1.06 ?m laser using a bulk-structured Bi2Te3 topological insulator", Journal of Optics 16, 085203(2014). CrossRef Y. Chen, et al., "Large Energy, Wavelength Widely Tunable, Topological Insulator Q-Switched Erbium-Doped Fiber Laser", IEEE Journal of Selected Topics in Quantum Electronics 20, 315(2014). CrossRef M. Wu et al., "Nanosecond Q -Switched Erbium-Doped Fiber Laser With Wide Pulse-Repetition-Rate Range Based on Topological Insulator", IEEE Journal of Quantum Electronics 50, 393(2014). CrossRef J. Lee et al., "Dry Etched Waveguide Laser Diode on GeOI", IEEE Journal of Selected Topics in Quantum Electronics 21, 31(2015). CrossRef J. Li et al., "3-?m mid-infrared pulse generation using topological insulator as the saturable absorber ", Optics Letters 40, 3659(2015). CrossRef Z. Luo et al., "Topological-Insulator Passively Q-Switched Double-Clad Fiber Laser at 2 ?m Wavelength", IEEE J. Sel. Topics Quantum Electron 20, 0902708 (2014). CrossRef M. C. Paul, A. Dhar, S. Das, A. A. Latiff,M. T. Ahmad,and S. W. Harun, "Enhanced Erbium?Zirconia?Yttria?Aluminum Co-Doped Fiber Amplifier" IEEE Photonics Journal 7, 7100408 (2015). CrossRef H. Liu et al., "Femtosecond pulse generation from a topological insulator mode-locked fiber laser", Optics Express 22, 6868 (2014). CrossRef Z. Sun, T. Hasan, and A. C. Ferrari, "Ultrafast lasers mode-locked by nanotubes and graphene", Physica E 44, 1082(2012). CrossRef J. Lee, M. Jung, J. Koo, C. Chi, and J. Lee, "Dry Etched Waveguide Laser Diode on GeOI", IEEE Journal of Selected Topics in Quantum Electronics 21, 0900206 (2015). CrossRef H. Ahmad, A. Z. Zulkifli, K. Thambiratnam, and S. W. Harun, "2.0-?m Q-Switched Thulium-Doped Fiber Laser With Graphene Oxide Saturable Absorber", IEEE Photonics Journal5, 1501108(2013). CrossRef